Qualifications, Employment and the Value of Human Capital, 1986-2001 - Dean Hyslop; Dave Mare; Jason Timmins (New Zealand Government, The Treasury, 2003)
This paper summarises the changing nature of qualifications across the working age population in New Zealand over the period from 1986 to 2001, and investigates the relationships between the changing qualification distribution and employment and income. First, the results confirm that there was a general upskilling of the population, as measured by formal educational qualifications. Second, we examine patterns of qualification change and employment growth measured in job groups, and find that the upskilling of the population occurred across a wide range of job-groups. Also, although the results show the employment growth was strongest in job-groups with high initial levels of skilled workers, employment growth is only weakly related to upskilling. Third, we decompose the change in the value of human capital into contributions due to changes in the qualification mix, changes in the (economic) returns to qualifications, and the interaction between these two factors. The value of human capital increased by 20% over the period: about 75% of this increase can be attributed to increasing incomes holding constant the mix of qualifications, 15-20% to an increasing skill mix, and the residual to interaction effects.
Keywords: J21; J24; 330; Qualifications; Upskilling; Human Capital; Employment Growth; Incomes; New Zealand